Construction and optoelectronic applications of organic core/shell micro/nanostructures. Issue 12 (21st September 2020) - Zhuo, Ming-Peng; Wang, Xue-Dong; Liao, Liang-Sheng
Abstract : This review summarizes recent advances in organic core–shell structures from the aspects of fabrication methods and optoelectronic applications, providing inspiration for the rational design of organic core–shell structures with desired performance. Abstract : Organic core/shell micro/nanostructures (OCSSs) not only demonstrate outstanding physicochemical features, but also provide an expanded heterojunction area to enhance their thermal stability and charge-carrier mobility, which are beneficial to high-performance optoelectronic applications. However, the fine synthesis of OCSSs is still a considerable challenge because of the difficulty in realizing the perfect lattice matching and surface-interface energy balance. Hence, it is suggested that the growth mechanism and corresponding optoelectronic devices are imminently investigated and developed. A summary of recent advances in the preparation and the optoelectronic application of OCSSs are necessary for readers to get a more comprehensive understanding on their rational design and controllable construction to achieve superior performance devices. Herein, recent breakthroughs in OCSSs are introduced, including the organic molecular design, preparation methods, and optoelectronic applications.